DESAIN SISTEM POMPA AIR SOLAR PHOTOVOLTAIC (SPV) 125 WATT DI DESA RAMBAT, KECAMATAN GEYER, KABUPATEN GROBOGAN - Harmini, Harmini; Nurhayati, Titik (Elektrika, 2018)
In this research will be designing a prototype of a water pump system using solar photovoltaic (SPV) that is designing a SPV in accordance with the needs of PV with the capacity of water pump. The power generated by the photovoltaic system will be used to drive the water pump. One of the areas in Central Java region that have not received water source is Dusun satreyan, Rambat Village Geyer Subdistrict Grobogan District. The solar photovoltaic (SPV) water pump system is de-signed using SPV panels, Solar Charge Controller, Battery and Inverter for the needs of 1 family head with water capacity per day is 300 Liter. The water pump capacity is 125 Watt, the number of SPV panels of 2 each with a capacity of 100 Wp, battery capacity, solar charge controller and inverter is 60 Ah, 10.42 Ampere and 12 volts DC 220 VAC. The average effi-ciency rating of the SPV water pump system as a whole is 61.18%Keywords: MPPT,Solar Photovoltaic, Tracking.